2006
DOI: 10.1002/ajh.20510
|View full text |Cite
|
Sign up to set email alerts
|

Acquired amegakaryocytic thrombocytopenic purpura

Abstract: Acquired amegakaryocytic thrombocytopenia is an unusual hematologic disorder characterized by thrombocytopenia in association with markedly diminished bone marrow megakaryocytes. We report a case that responded to treatment with cyclosporine but not to IL-11. The bone marrow biopsy, repeated after resolution of thrombocytopenia, showed normal number of megakaryocytes. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…These defects in maturation and differentiation may be idiopathic or caused by exogenous (virus, toxin, or drug exposure) [1] or immune (humoral or cellular) [1,2,4] mechanisms. Antibodies to CFU-MK (megakaryocyte progenitor) have been described mainly in association with other autoimmune diseases, such as systemic lupus erythematosus [1,4,5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These defects in maturation and differentiation may be idiopathic or caused by exogenous (virus, toxin, or drug exposure) [1] or immune (humoral or cellular) [1,2,4] mechanisms. Antibodies to CFU-MK (megakaryocyte progenitor) have been described mainly in association with other autoimmune diseases, such as systemic lupus erythematosus [1,4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections, toxins, drug exposure, lymphoproliferative disorders, thymoma, and rheumatologic diseases have all been described, mostly as individual case reports [2,5,6,8,10,11]. The herpesvirus EBV may have various hematologic complications such as Burkitt lymphoma, autoimmune hemolytic anemia, hemophagocytic syndrome, or thrombocytopenia [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once AATP is diagnosed, a therapeutic trial of cyclosporine, with or without antithymocyte globulin (ATG), is indicated [1]. Allogeneic bone marrow transplantation (BMT) is considered to be an appropriate treatment for patients with refractory or progressive AATP, who are relatively young and have matched siblings [2].…”
mentioning
confidence: 99%
“…Of the drugs that the patient had received, both aspirin and allopurinol had previously been given to patients with AATP [1,3,4]. However, since it was impossible to show that none of the other drugs were associated with AATP, all medications were discontinued [5].…”
mentioning
confidence: 99%